Dynamics of gender equality: Analysis of the practice of ta‘līq al-ṭalāq in Morocco and Indonesia from the perspective of legal sociology - Nurul Izzati; Efrinaldi Efrinaldi; Hamda Sulfinadia; Rahmat Ryadhush Shalihin (An-Nisa’ Journal of Gender Studies, 2024)
The practice of taʿlīq al-ṭalāq faces implementation challenges due to differing social, cultural, and legal contexts, leading to variations in the protection of wives' rights in Islamic marriage in Indonesia and Morocco. This study aims to analyze and compare the practice in both countries to understand how Islamic family law is institutionalized, interpreted, and applied across different social settings. A qualitative descriptive-comparative method with content analysis of classical Islamic legal texts, regulations, and scholarly literature was employed to examine the influence of legal, cultural, and gender factors. Three key findings emerge. First, in Indonesia, taʿlīq al-ṭalāq has been institutionalized through marriage traditions, state regulations, and official registration, systematically bridging religious norms, local culture, and state law. Second, in Morocco, taʿlīq al-ṭalāq functions as a legal instrument for women's protection through anti-polygamy clauses, strengthening wives' autonomy and the state's role in achieving marital equality. Third, Indonesia emphasizes family stability through the husband's obligations, whereas Morocco prioritizes the protection of women's rights, reflecting divergent policy orientations in modern Islamic family law. The study concludes that Islamic family law is dynamic and contextual. Indonesia focuses on family stability, while Morocco focuses on the protection of women's rights; both represent adaptations to their respective socio-political contexts. This study enriches the sociology of law through its analysis of the plurality of Islamic family law and provides a practical reference for developing responsive policies concerning women's protection and the socio-religious context of society.